The effect of salinity gradient and heavy metal pollution on arbuscular mycorrhizal fungal community structure in some Algerian wetlands - Sidhoum, Warda (Array, 2020)
Algerian natural wetlands suffer from anthropogenic disturbances due to industrial development and urbanization. This study was designed to draw attention to arbuscular mycorrhizal fungi (AMF) distribution and community assemblages following heavy metal and salinity concentrations in two wetlands subjected to domestic and industrial effluents. Rhizospheric soil and roots of 18 plant species were collected in two wetlands along a decreasing salinity gradient. The results showed that 72.72% of plant species exhibit an association within arbuscular mycorrhizas (AM), and 36.36% a dual association between AM and dark septate endophytes (DSE). A total of 33 AMF morphospecies were distinguished on the basis of morphological criteria dominated by taxa belonging to Glomeraceae and Acaulosporaceae. Soil contamination was investigated by determining metallic trace elements (MTE) (Cd, Cu, Ni, Pb, Cr and Zn) using an atomic absorption spectrophotometer. Values of the pollution index revealed wetlands that were particularly polluted by lead. Two˗way ANOVA showed significant variations in metal content among sampling locations and transects. Principal component analysis showed that species richness, and mycorrhizal frequency were slightly affected by MTE. This opens possibilities for their utilization in polluted soil remediation.